Autonomic Internet of things for enforced demand management in smart grid - Ashraf, Qazi Mamoon; Chun, Yeow Yeoh; Khalaf, Ayesheh Ahrari; Al-Haddah, Ahmed; Habaebi, Mohamed Hadi; Wan Abdullah, Wan Razli; Yahya, Mohamed Razman (Science Publishing Group, 2017)
Recent research in the field of Internet of Things (IoT) has concentrated on the adaptation of the autonomic computing theory to make IoT self-sufficient and self-managing. The smart grid is one popular IoT application which can greatly benefit from the adoption of autonomy. In this paper, we propose the idea of enforced demand management (EDM) in smart grid as an implementation of the autonomic computing framework. Instead of allowing all consumer appliances to be active, the smart grid can actuate and control selected appliances remotely and autonomic-ally. This will allow the smart grid to be able to exercise some control over the load and consequently the demand it faces during peak hours of usage. Subsequently, the smart grid will be able to enhance efficiency and reliability. Furthermore, cellular network requirements for enabling such a method are also highlighted for the case of Long-Term-Evolution (LTE).